RELATIONSHIP BETWEEN BMI, PHYSICAL FITNESS & MOTOR SKILLS IN CHILDREN WITH DOWNS SYNDROME - Mahnoor; Sadaf Tubassam; Fareeha Kousar; Aadil Omer; Maria Arif; Muhammad Tahir (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background:Children with Down syndrome frequently experience particular difficulties with regard to their physical well-being and motor growth. The body mass index (BMI) measures body composition and weight status, whereas physical fitness measures general health and functional capacity.Objective:To evaluate the relationship between BMI, Physical fitness and motor skills in children with Downs syndrome.Methods:In our seven-month cross-sectional study, spanning December 2022 to June 2023, we evaluated 169 children between the ages of 6 to 11 (average age 7.96 ± 1.461 years). Participants were randomly selected The SAMU Disability Fitness Battery (SAMU-DISFIT) assessed physical fitness, encompassing Waist Circumference and BMI for Body Composition, the Time Up and Go Test for Motor Fitness, Deep Trunk Flexibility, Right and Left Hand Grip Strength, a 30-second Sit-Up, and a 10 Timed Stand Test for Musculoskeletal Fitness. Cardiorespiratory Fitness was evaluated with the 6-minute walk test. Motor skills assessment was conducted using the Total Gross Motor Development-2 (TGMD-2) test. Data were analyzed using SPSS version 25.0Results:The results revealed the following associations: "Body Composition": Waist Circumference displayed a weak negative correlation (-0.205). "Motor Fitness": The Time up and Go Test showed a moderate negative correlation (-0.263). "Musculoskeletal Fitness": Grip Strength in the Right Hand had a significant strong positive correlation (0.559), and in the Left Hand, it showed a moderate positive correlation (0.484). Deep trunk Range of Motion (ROM) displayed a strong positive correlation (0.644). These findings underline the complexity of the relationship between BMI and various types of physical fitness and the need of taking several fitness factors into account when assessing an individual's overall health.Conclusion: The study found a negative association between BMI and physical fitness and mobility. Underweight children with Down syndrome demonstrated better physical fitness and mobility compared to overweight children. These findings emphasize the importance of weight management for optimizing physical well-being in individuals with Down syndrome.